Human hip–ankle coordination emerging from multisensory feedback control - Hettich, Georg; Assländer, Lorenz; Gollhofer, Albert; Mergner, Thomas (Human movement science, 2014)
•Hip–ankle motor coordination in humans and model simulations were compared.•Sensory-derived postural reactions produced the coordination in the model.•Good correspondence between the human and simulation data was found.•This is evidence that sensory integration may contribute to human interlink coordination.•Repeating the experiments in a humanoid robot confirmed the simulation results. Human sensorimotor control involves inter-segmental coordination to cope with the complexity of a multi-segment system. The combined activation of hip and ankle muscles during upright stance represents the hip–ankle coordination. This study postulates that the coordination emerges from interactions on the sensory levels in the feedback control. The hypothesis was tested in a model-based approach that compared human experimental data with model simulations. Seven subjects were standing with eyes closed on an anterior–posterior tilting motion platform. Postural responses in terms of angular excursions of trunk and legs with respect to vertical were measured and characterized using spectral analysis. The presented control model consists of separate feedback modules for the hip and ankle joints, which exchange sensory information with each other. The feedback modules utilize sensor-derived disturbance estimates rather than ‘raw’ sensory signals. The comparison of the human data with the simulation data revealed close correspondence, suggesting that the model captures important aspects of the human sensory feedback control. For verification, the model was re-embodied in a humanoid robot that was tested in the human laboratory. The findings show that the hip–ankle coordination can be explained by interactions between the feedback control modules of the hip and ankle joints.